The effect of the Montessori program using physical activity games in enhancing the sensory-motor perception abilities of kindergarten children aged 5 to 6 years - Intisar Ahmed Othman; Lamyaa Hassan Mohammed; Riyadh Alsaeed; Sarah Sami Shabib (University of Basrah, 2024)
The research aims to propose an educational approach inspired by Montessori's method using motor games to develop sensory motor skills in children aged (5-6) years, and to identify the impact of using Montessori's method with motor games in developing some cognitive sensory motor skills for children. The experimental method was used with the matched group design. The sample represented children from the Braum Al-Amal Nursery in Basra, who were selected to take the Haywood test to measure cognitive sensory motor abilities. It was concluded that Montessori's method using motor games contributed to the development of sensory motor skills and helped in enhancing overall and partial visual perception for children. The child learned about parts of the body, distinguished between body sides, and helped in enhancing balance and spatial awareness. The method also aided in teaching the child how to determine location. It was recommended to benefit from the Montessori method in developing motor and cognitive abilities, and to introduce specific courses for preschool teachers in teaching the Montessori method. Key words: Montessori method, motor games, sensory motor perception, preschool education, teaching methods